2007
DOI: 10.2134/jnrlse2007.36111x
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Field School Curriculum Using Modularized Lessons and Authentic Case-Based Learning

Abstract: University course evaluations are replete with student comments expressing frustration with taking time out of work, paying money for, and putting energy into field education projects that lack authentic “real‐world” problem‐solving objectives. Here, we describe a model for field school education that borrows on pedagogical tools such as problem‐based learning, hands‐on instruction, field‐based education, and teaching through research, and employs modularized teaching in a way that incorporates numerous resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…A context such as this requires not only engaging activities to capture and maintain student motivation, which is a primary determinant of student retention, 5 but also a substantial amount of instructor guidance and feedback. [5][6][7][8][9][10][11] Within formal educational structures, students have many opportunities to answer questions but few opportunities to pose them. 12 In the sciences, inquiry is an especially important skill that instructors try to help their students develop, yet students are rarely engaged in this activity due to the instructor workload challenges.…”
Section: Introductionmentioning
confidence: 99%
“…A context such as this requires not only engaging activities to capture and maintain student motivation, which is a primary determinant of student retention, 5 but also a substantial amount of instructor guidance and feedback. [5][6][7][8][9][10][11] Within formal educational structures, students have many opportunities to answer questions but few opportunities to pose them. 12 In the sciences, inquiry is an especially important skill that instructors try to help their students develop, yet students are rarely engaged in this activity due to the instructor workload challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of poor teaching included using a lecture‐only teaching method, disengaged students and instructors, lack of peer‐to‐peer interaction, and lack of student‐to‐instructor interaction (Seymour and Hewitt, 1997). Rea and Hodder (2007) further stated that students express frustration in courses that lack authentic “real‐world” problem‐solving objectives. In order to actively engage students in their own learning and improve science instruction, Springer, Stanne, and Donovan (1999) argued for the need to shift the emphasis from teacher‐centered to more learner‐centered approaches.…”
mentioning
confidence: 99%
“…Some of the research has found that case studies increase students’ ethical awareness (Lundeberg et al, 2002) and lead to significant improvement in students’ understanding (Dori et al, 2003), whereas other research has suggested no significant differences in performance between the traditional and case study groups (Antepohl and Herzig, 1999; Hoag et al, 2005). However, other research has suggested that when learning via the case study method students report higher satisfaction (Antepohl and Herzig, 1999), have increased attendance (Hoag et al, 2005), and give positive evaluations of the course (Dinan, 2002; Rea and Hodder, 2007). These results are promising in terms of the impact of case teaching method on student satisfaction and learning.…”
mentioning
confidence: 99%